Synthesis of 2[N-Cinnamlideneamino]-5-Nitro Phenol and Its Metal(II) Complexes and Evaluation of Their Antitumor Activities - FAWZY EL-HUSSEINY, AMEL (Asian Journal of Chemistry, 2009)
The preparation of a series of metal(II) complexes (Zn, Cu, Co and Ni) with 2[N-(cinnamlidene)amino]-5-nitro phenol as a novel ligand and their biological evaluation against six species of pathogenic yeasts (Candida albicans, C. fructus, C. glabrata, C. oleophila, C. parapsilosis and C. tropicalis) are described. All new compounds were fully characterized by elemental analyses, spectroscopic measurements (IR, UV-vis, NMR, ESR and EIMS) as well as thermal and magnetic susceptibility measurements. Studies revealed that HL ligand acts as bidentate through N and O atoms. Zn(II) and Co(II) complexes exhibited tetrahedral geometry while Cu(II), Ni(II) are octahedral. Both Co(II) and Zn(II) complexes exhibited potential antitumor activities and the latter showed promising cytotoxicity (70-82 % cell mortality) and it may be considered a new antitumor agents.